The cold chain question: effect of beef trim cold chain management on ground beef quality, shelf life, and palatability - Stickley, Samuel Franklin (My University, 2026)
Ground beef is one of the most widely consumed and economically important beef products in the United States and plays a critical role in carcass utilization by providing an outlet for lean and fat trimmings generated during fabrication. Because domestic lean trim supplies are limited, frozen trim remains an important component of the beef supply chain for storage, transport, and import applications. Although freezing improves logistical flexibility, it may also alter the functional properties of meat and influence the resulting ground beef. Therefore, the objective of this study was to evaluate the impact of varying combinations of fresh, frozen, and thawed beef trim on the shelf life, quality characteristics, and palatability of ground beef. Beef trim of varying lean percentages (50%, 80%, and 90%) and cold chain states (fresh, thawed, and frozen) was ground and combined to create 10 unique treatments of 80% lean ground beef. Product was formed into 151g patties, overwrapped, and subjected to 5 days of simulated retail display. Trained visual panel redness and discoloration scores and objective color measurements were collected daily throughout display. Consumer visual panels evaluated packages on day 3 of display and consumer taste panels, trained taste panels, shear force, texture profile analysis, and TBARS were conducted on patties after 3 days of display. The cold chain state of trim has substantial effects on both visual acceptability and eating quality. Patties containing fresh trim or fresh combined with frozen or thawed trim were rated highest (P < 0.05) for appearance and purchase intent, whereas exclusively frozen treatments were least preferred (P < 0.05). Trained panelists detected treatment differences in redness during early and mid-display, with treatments containing frozen lean trim declining the most rapidly, although discoloration scores did not differ among treatments. Frozen-only treatments declined the most rapidly (23.1% by day 1) in a* values, and treatments containing frozen lean trim accumulated greater metmyoglobin percentages during later display. In contrast, thawed trim treatments generally behaved similarly to fresh treatments, maintaining redness and a* value across display, without a sharp decline. Trained panelists reported greater (P < 0.05) oxidized off-flavor in frozen only treatments and consumer beef-flavor liking scores generally favored treatments containing fresh or thawed trim. Lipid oxidation measured by TBARS closely matched these sensory responses, as treatments produced from frozen lean trim had greater (P < 0.05) oxidation, and treatments from entirely fresh trim had the least (P < 0.05). Frozen-only treatments were rated as more tender but lower (P < 0.05) in texture liking and produced the lowest shear force and cohesiveness values, indicating a softer, less cohesive product. The most severe quality losses occurred when trim was ground directly from the frozen state, particularly when the lean component remained frozen. Treatments produced from fresh or thawed trim maintained greater color stability, lower oxidation, more desirable flavor, and better structural integrity. These results indicate that frozen trim can remain part of the beef supply chain without necessarily compromising final product quality, provided it is thawed prior to grinding rather than ground while still frozen.
Keywords: Ground beef; Beef trim; Shelf life; Palatability; Consumer; Color of meat